Integrated veterinary-medical activity on characterization of shigatoxin producing Escherichia coli. (13th November 2019) - Bertasi, B; Finazzi, G; Colombo, R; Vignati, C; Dodaro, A; Spelta, C; Romanò, A; Tel, F; Ardissino, G L; Luini, M V
Abstract: Background: Shiga toxin-producing Escherichia coli (STEC) are an important public health concern as they cause severe conditions (bloody diarrhea and hemolytic uremic syndrome - HUS) and have epidemic potential. Cattle are the main reservoir for the highly virulent STEC O157 strain, and other HUS-associated non-O157 strains. This study aimed to characterize strains from animals and humans and to compare their molecular profiles. Animal isolates were tested for the presence of virulence factors correlated to their pathogenic potential. Methods: 74 STEC human isolates from 43 clinical cases (sporadic or epidemic) and 270 animal isolates from feces from 62 cattle farms were collected. Epidemiological investigation to collect environmental and suspected food samples was carried out for 22 cases. All isolates were typed with PFGE and their serotype was defined by Real-Time PCR. Animal isolates were also tested for the presence of subAB, saa, tia, cfk, adfO, hlyA, efaI1-lifA5'3', and toxB virulence genes. Results: O157 was detected in 44% of human cases, other relevant serogroups O26, O111, O103, O145 in 21, 9, 5 and 5% of cases, respectively. The source of infection was identified in one case (cheese contaminated by a O157 strain). Among animal isolates 2, 0.7, 0.7 and 0.3% were identified as O157, O11, O113, and O145, respectively. PFGE highlighted a high heterogeneicity among animal strains, however no pulsotype common to cattle and clinical isolates was found. adfO, cfk, efaI1-lifA5'3' and toxB were found significantly correlated to eae (intimin). Conclusions: Human and cattle strains were not correlated, however STEC diversity in cattle was very high and included some strains potentially pathogenic to humans. For this reason, upholding an integrated surveillance is very important. Key messages: Serotypes relevant to human health were found in cattle in a small but not negligible frequence. No direct correlation was found between animal and clinical isolates.